Microplastic Contamination on the Beaches of South China - Chai, Bingwen; Li, Yanping; Wang, Li; Zhang, Xiao-Tan; Wan, Yi-Ping; Chen, Fengyuan; Ma, Jie; Lan, Wenlu; Pan, Ke (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.